1976
DOI: 10.1210/jcem-43-5-1128
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Hypercortisolism without Cushing's Syndrome

Abstract: A very high cortisol production rate (CPR) with elevated plasma ACTH was found in a hypertensive, hypokalemic, but otherwise healthy male patient. There were no symptoms or signs of Cushing's syndrome. The hypercortisolism appeared to be of the pituitary dependent type. During the follow-up of 36 months, no changes in outward appearance occurred, notwithstanding persistent hypercortisolism. The possibility of either Conn's syndrome or of an enzymatic defect in steroidogenesis could be ruled out. One of the thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
69
0
5

Year Published

1993
1993
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(76 citation statements)
references
References 14 publications
2
69
0
5
Order By: Relevance
“…The syndrome of familiar glucocorticoid resistance, first described in 1976, is a disorder characterized by hypercorticosolism without Cushingoid features (Vingerhoeds et al 1976, Chrousos et al 1982. Since then, over ten kindreds and sporadic cases have been reported (Iida et al 1985, Lamberts et al 1986, 1992, Nawata et al 1987, Vecsei et al 1989, Hurley et al 1991, Karl et al 1993, 1996, Malchoff et al 1993.…”
Section: Gr Mutationsmentioning
confidence: 99%
“…The syndrome of familiar glucocorticoid resistance, first described in 1976, is a disorder characterized by hypercorticosolism without Cushingoid features (Vingerhoeds et al 1976, Chrousos et al 1982. Since then, over ten kindreds and sporadic cases have been reported (Iida et al 1985, Lamberts et al 1986, 1992, Nawata et al 1987, Vecsei et al 1989, Hurley et al 1991, Karl et al 1993, 1996, Malchoff et al 1993.…”
Section: Gr Mutationsmentioning
confidence: 99%
“…Primary cortisol resistance, first described by Vingerhoeds et al (1), is a rare inherited disorder characterized by hypercortisolism without Cushingoid features. Clinical manifestations, if any, are secondary to excess circulating nonglucocorticoid adrenal steroids (1)(2)(3)(4)(5)(6)(7)(8)(9)(10), which cause hypertension with hypokalemia (2) and/or signs of androgen excess (7,9,10).…”
Section: Introductionmentioning
confidence: 99%
“…They show a wide spectrum of clinical symptoms, such as hypertension, hypokalemic alkalosis (2), fatigue, and hyperandrogenism (3). Vingerhoeds et al (2) reported a father and a son with GC resistance, and from then until now 20 additional patients and family members with this syndrome have been described (4).…”
mentioning
confidence: 99%